2017
DOI: 10.1177/1075547017707765
|View full text |Cite
|
Sign up to set email alerts
|

Using Weight-of-Experts Messaging to Communicate Accurately About Contested Science

Abstract: Research indicates that balanced news coverage of opposing scientific claims can result in heightened uncertainty among audiences about what is true. In this study, we test the ability of a weight-of-experts statement to enhance individuals’ ability to distinguish between more versus less valid claims. An experiment found that the weight-of-experts narrative led participants to greater certainty about what scientists judged to be true, which made participants more likely to “buy in” to that judgment themselves. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…While the majority of attention to consensus messaging has focused on climate change, studies have also explored other scientific issues. In support of the GBM, studies have found that interventions which change participants’ perception of a scientific consensus also change their personal beliefs in relation to vaccination [ 20 , 42 , 43 ], pharmaceutical pollution of waterways [ 44 ], scientific whale research and the link between blood type and personality [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of attention to consensus messaging has focused on climate change, studies have also explored other scientific issues. In support of the GBM, studies have found that interventions which change participants’ perception of a scientific consensus also change their personal beliefs in relation to vaccination [ 20 , 42 , 43 ], pharmaceutical pollution of waterways [ 44 ], scientific whale research and the link between blood type and personality [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that people's perceptions of scientific consensus-the extent to which scientists agree on a scientific issue-predict and influence their beliefs about the issue (Cook & Lewandowsky, 2016;Ding, Maibach, Zhao, Roser-Renouf, & Leiserowitz, 2011;Dixon & Clarke, 2013;Dunwoody & Kohl, 2017;Kohl et al, 2016;Lewandowsky, Gignac, & Vaughan, 2013;McCright, Dunlap, & Xiao, 2013;van der Linden, Clarke, & Maibach, 2015;. That is to say, those who estimate greater consensus among scientists on the existence of a scientific phenomenon (e.g., anthropogenic climate change) or causality (e.g., vaccine-autism link) are more likely to accept and be certain about the scientific phenomenon or causality.…”
Section: Introductionmentioning
confidence: 99%
“…Developing highly tailored campaigns and interventions for specific target audiences is likely to yield the most promising results in changing the publics' knowledge, attitudes, and behaviors toward potential environmental breast cancer risks (19). When communicating uncertain scientific findings to the public, one effective strategy is to present multiple claims and then state how many experts believe each claim, generating perceptions of certainty about a scientific claim (20). If a breast cancer risk message conveys the number of scientists who believe there is a need to take environmental risks seriously, this might motivate members of the public to engage in precautionary behaviors such as avoiding consumer products that contain chemical toxins.…”
Section: Individual Focus: the Bottom-up Approachmentioning
confidence: 99%